Sistem Pendukung Keputusan Optimasi Lahan Beririgasi (Studi kasus: DI Bondoyudo, Jawa Timur) - , afik hardanto, Prof. Dr. Ir. Sigit Supadmo Arif, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The allocation management of irrigation water that was based on consept that irrigation water was a common pool resources and the service based on the dialogue to the most important matter in his implementation, then in planning the transaction will happen between the provider and the user of the service. Decision Support System (DSS) was used to help the allocation transaction of the provisions of irrigation water in determining the optimum area in each piece of the service with the limitation and the land of water resources that were available. The research case study was carried out in the Bondoyudo Irrigation Region, East Java. Thomas-Fiering Model was used to predict the data of rain and debit. Linear Programming Model was used to optimize the crop pattern. Software development was used by the Visual Basic 6.0 and the database management was used MySQL. Results of the research showed that the model of Thomas-Fiering that was used appropriate to generate the data with the value of rain of the evaluation in 1 st MT (r= 0.905, RMS= 15.84, and ME= -8.59), 2 nd MT (r= 0.683, RMS= 5.70, and ME= -0.06), and 3 rd MT (r= 0.685, RMS= 26.31, and ME= 8.89). The value of the evaluation of debit model was obtained by the value r= 0.82, RMS= 2498.05, and ME= -375.59. Optimum results of crop pattern was obtained in accordance with input resources and limit condition that were used in each time. Results of the sensitivity analysis were obtained that tolerance for the constrain functions in each condition (e.g., 2 nd MT in 2010, rice (-) 2,75 and (+) 30,04, polowijo (-)13.45 and (+) 2,75, the citrus fruit (-)5.57 and (+) 1E+30, and sugar cane (-)3.00 and (+) 1E+30. Whereas for the limitation variable, that is the area limitation of the total piece with shadow price 16.15 (-253,87 and +790,25), the availability of debit 0,96 (-450,44 and + 868,25), the maximum area of the citrus fruit and sugar cane depended on the percentage of the area that was permitted.